The effect of a magnetic field on the motion of electrons for the field emission process description - Lebedynskyi, S.O.; Miroshnichenko, V.I.; Kholodov, R.I.; Baturin, V.A. (Вопросы атомной науки и техники, 2015)
The Schrödinger equation is solved for the wave function of an electron moving in a superposition of external constant and uniform electric and magnetic fields at an arbitrary angle between the field directions. The changing of the potential barrier under influence of the magnetic field parallel to the metal surface is shown.